The Impact Of Ancient Chinese Mythology On The Development Of Eastern Philosophy - Tursunov Muhiddin Boltaevich (Global Scientific Publishing, 2024)
This article examines the influence of Chinese mythology on Eastern philosophy, focusing on how mythological narrations shape philosophical concepts such as harmony and moral norms. It was discussed how myths serve as a basis for understanding the interaction of man and nature, as well as their role in the development of philosophical systems such as Daoism and Confucianism
Keywords: Chinese mythology; Eastern philosophy; Taoism; Confucianism